Identifikasi Kebutuhan Pendidikan Melalui Keunggulan Potensi Daerah - Irham Iskandar (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
The main objective of this research is to identify what education is in line with the advantages of regional potential, namely through specific typologies, approaches to the pattern of economic growth relations and the human development index and location quotient. This type of research method is development research, namely research aimed at developing research findings or previous theories, both for the purposes of pure science and applied sciences and so on. The data used in this study is secondary data in the form of data in the form of annual reports on Aceh economic statistics in 2012-2016 in the form of GRDP data, economic growth, per capita income, human development index obtained from the Central Statistics Agency. The results of the study show that the identification of education is appropriate to the potential in disadvantaged areas, namely Aceh Singkil District such as electricity and gas procurement, financial and information services, government administration, land and compulsory social security, as well as health services and social activities; South Aceh Regency such as construction, information and communication, as well as government administration, land and compulsory social security; North Aceh Regency such as agriculture, forestry and fisheries; mining and excavation; and processing industry; Southwest Aceh District such as construction; health services and social activities; and other services; Aceh Tamiang Regency such as fisheries, forestry and fisheries; mining and excavation; and other services; Nagan Raya Regency such as agriculture, forestry and fisheries; and mining and quarrying; and Aceh Jaya Regency such as construction, transportation and warehousing, as well as government administration, defense and compulsory social security. Keywords: standard typology, economic growth, human development index, and location quotient